2021
DOI: 10.1101/2021.06.02.21258214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eating disorder symptoms and their associations with anthropometric and psychiatric polygenic scores

Abstract: Background. Eating disorder (ED) symptoms are prevalent in the general population, but their shared genetic underpinnings with psychiatric, metabolic, and anthropometric traits are not known. Here, we examined if polygenic scores (PGS) of traits associated with anorexia nervosa are also associated with adolescent ED symptoms in the Avon Longitudinal Study of Parents and Children (ALSPAC). Methods. We calculated PGS for 25 traits (16 psychiatric, 4 metabolic, and 5 anthropometric) and investigated their associa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Genetic studies have found commonalities between anorexia nervosa, other psychiatric disorders and metabolic variations (7) . Interestingly, binge-type eating disorders, anorexia nervosa and constitutional thinness differ in their associations with anthropometric and psychiatric polygenic scores supporting the idea that the same general diagnostic category (eating disorder) may be underpinned by different processes (8,9) . Also, people with binge-eating disorders (in contrast to people with anorexia nervosa) share a proportion of their genetic profile with ADHD (10) .…”
Section: Predisposing Factorsmentioning
confidence: 82%
“…Genetic studies have found commonalities between anorexia nervosa, other psychiatric disorders and metabolic variations (7) . Interestingly, binge-type eating disorders, anorexia nervosa and constitutional thinness differ in their associations with anthropometric and psychiatric polygenic scores supporting the idea that the same general diagnostic category (eating disorder) may be underpinned by different processes (8,9) . Also, people with binge-eating disorders (in contrast to people with anorexia nervosa) share a proportion of their genetic profile with ADHD (10) .…”
Section: Predisposing Factorsmentioning
confidence: 82%